'Is totally endoscopic coronary artery bypass grafting compared with minimally invasive direct coronary artery bypass grafting associated with superior outcomes in patients with isolated left anterior descending disease?'. (September 2020) - Manuel, Lucy; Fong, Laura S.; Wolfenden, Hugh; Bassin, Levi
Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was 'Is totally endoscopic coronary artery bypass grafting compared with minimally invasive direct coronary artery bypass grafting associated with superior outcomes in patients with isolated left anterior descending disease?' Altogether more than 118 papers were found using the reported search, of which 4 represented the best evidence to answer the clinical question, which included 2 prospective cohort studies and 2 retrospective observational studies. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers were tabulated. There is a significant variation within the MIDCAB and TECAB techniques amongst the studies-including the experience of the surgeon, use of cardiopulmonary bypass, patient selection, and target vessel grafting strategies-highlighting the complexity of comparing these two minimally invasive procedures. Operative times were comparable across all studies, with TECAB patients having higher transfusions rates and conversion rates to either a median sternotomy or MIDCAB procedure. Overall safety was comparable between the two cohort groups, with similar length of stay and 30-day mortality. However, the TECAB group were more likely to require re-operation for bleeding and reintervention for early revascularisation with greater total hospital costs than the MIDCAB patients. Based on the available evidence, we conclude that TECAB is associated with a higher rate of transfusions, conversion to median sternotomy or MIDCAB, early graft failure and reintervention compared to the MIDCAB approach. We advise caution in adopting a TECAB approach. Highlights: Coronary Artery Bypass Grafting remains the gold standard for complex multi-vessel disease. Demand for minimally invasive and robotic procedures is increasing. Controversy remains regarding the optimal method for robotically assisted coronary grafting. Overall safety is comparable between TECAB and MIDCAB. TECAB is associated with a higher rate of early graft failure and reintervention.